New species and new records of deepwater munidid squat lobsters from north-western Australia: Onconida, Bathymunida, Crosnierita, Plesionida and Torbenella - Ahyong, Shane T.; Taylor, Joanne; Mccallum, Anna W. (Zootaxa, 2013)
Seven species of Munididae are reported from the continental margin of north-western Australia. Three species are new to science: Crosnierita adela sp. nov., Onconida ariel sp. nov. and Plesionida aurelia sp. nov., each presently known only from Western Australia. Four species are reported for the first time from Australian waters, Bathymunida balssi Van Dam, 1838, Bathymunida dissimilis Baba & de Saint Laurent, 1996, Crosnierita yante (Macpherson, 1994) and Torbenella orbis (Baba, 2005). Keys to the world species of the genera represented are provided.